Kylie's song - Sheehan, Patty, 1945-; Maeno, Itoko (Santa Barbara, CA : Advocacy Press, 1988)
Kylie, a koala who loves to sing but is made unhappy by the other animals who laugh at her for being different, ventures out in search of a new life and finds a nice surprise.
Map on endpapers.
3.3
K-3
Keywords: Koala -- Fiction; Self-confidence -- Fiction; Prejudices -- Fiction; Conduct of life -- Fiction; Koalas -- Fiction; Self-confidence -- Fiction; Prejudices -- Fiction; Conduct of life -- Fiction